Pembelajaran Bahasa Indonesia berbasis Eko-Kultural untuk Penguatan Edu-Wisata di Kawasan Taman Nasional Bromo Tengger Semeru - Ahmad Syukron; Arief Rijadi (Belajar Bahasa: Jurnal Ilmiah Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
Indonesian language learning is the right vehicle for presenting content-based learning because it is text-based learning. Recently, eco-culture has become a trend again as evidenced by various things being built and branded as policies, technology, products, goods and services based on eco-culture. In practice, Indonesian language learning in schools has the potential to be designed as content-based learning with an eco-cultural approach. Through the integration of Indonesian language learning with content based on an eco-cultural approach, it is hoped that Indonesian language learning in schools will provide support for the development of eco-cultural-based edu-tourism in Indonesia. Eco-Cultural Based Indonesian Language Learning to Strengthen Edu-Tourism in the Bromo Tengger Semeru National Park Area" has urgency and relevance to the direction of research focuses at the University of Jember and supports national development schemes designed by the government.